PENGARUH ATTITUDE TOWARD BEHAVIOR, SUBJECTIVE NORM, PERCEIVED BEHAVIORAL CONTROL PADA INTENTION WHISTLEBLOWING - Khanifah Khanifah; Muhammad Choirul Anam; Ernawati Budi Astuti (Universitas Wahid Hasyim, 2017)
Abstract This study aims to examine and analyze the influence of attitude toward behavior, subjective norm, perceived behavioral control on whistleblowing intention. Collecting data in this study through questionnaires and conducted on 39 respondents who were auditors working at the Regional III Financial Services Authority (OJK) office in Central Java and Yogyakarta Special Region. Data analysis techniques in this study were processed using SPSS version 21. The results of this study indicate that attitude toward behavior has a positive effect on whistleblowing intention, subjective norm has a positive effect on whistleblowing intention, and perceived behavioral control has a positive effect on whistleblowing intention.Keyword: attitude toward behavior, subjective norm, perceived behavioral control, intention whistleblowing.AbstrakPenelitian ini bertujuan untuk menguji dan mengalisis pengaruh attitude toward behavior, subjective norm, perceived behavioral control pada intention whistleblowing. Pengumpulan data dalam penelitian ini melalui penyebaran kuesioner dan dilakukan pada 39 responden yang merupakan auditor yang bekerja di kantor Regional III Otoritas Jasa Keuangan (OJK) Jawa Tengah dan Daerah Istimewa Yogyakarta. Teknik analisis data dalam penelitian ini diolah dengan menggunakan program SPSS versi 21. Hasil penelitian ini menunjukan bahwa attitude toward behavior berpengaruh positif pada intention whistleblowing, subjective norm berpengaruh positif pada intention whistleblowing, dan perceived behavioral control berpengaruh positif pada intention whistleblowing.Kata Kunci: attitude toward behavior, subjective norm, perceived behavioral control, intention whistleblowing.